Tribological Behaviour and Microstructure of an Aluminium Alloy-Based g-SiC Hybrid Surface Composite Produced by FSP - Jun Liang Tan; Kia Wai Liew (Lubricants, 2023)
In this work, the microstructure and wear characteristics of a surface-reinforced composite based on an aluminium alloy with a mixture of graphene nanoplatelets (GNP) and silicon carbide (SiC), referred to as g-SiC, fabricated by Friction Stir Processing (FSP), are investigated. To further improve the tribological performance, different volume fractions (0 vol%, 5 vol%, 10 vol% and 15 vol%) of g-SiC-reinforced aluminium alloy are prepared by FSP. It is concluded that the Friction Stir Processed (FSPed) AA5083/g-SiC (15 vol%) specimen has optimum reduction in average friction coefficient (61.13%) and optimum reduction in specimen weight (72.97%). In summary, such hybrid reinforcements effectively improve the mechanical and tribological properties of metals with minimal negative impact on the environment and humans, while reducing material loss and overall manufacturing costs.